2012
DOI: 10.1093/mnras/sts008
|View full text |Cite
|
Sign up to set email alerts
|

Deep hard X-ray survey of the Large Magellanic Cloud

Abstract: Results of the deep survey of the Large Magellanic Cloud (LMC), performed with the INTEGRAL observatory, are presented. The long exposure (∼ 7 Ms) allowed us to detect twenty one sources in this sky region: ten belonging to the LMC itself (7 HMXBs, 2 PSRs, 1 LMXB), six of extragalactic origin and three belonging to other galaxies from the Local Group -the Milky Way (2 sources) and Small Magellanic Cloud (1 source). Four new hard X-ray sources of these 21 ones were discovered during the survey in addition to IG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
0
15
0
2
Order By: Relevance
“…Nevertheless, taking into account a peculiar property of LMC X-4 (the source periodically goes to the "off"-state) and using the corresponding subset of revolutions, Grebenev et al (2013) showed that the persistent hard X-ray emission actually originates from the sky region coinciding with the position of another X-ray pulsar, EXO 053109-6609.2. This conclusion was supported by an independent detection of this source in the standard X-ray energy band by the INTEGRAL/JEM-X telescope, which allowed Grebenev et al (2013) to reconstruct the source spectrum in a broad energy band and demonstrate that it is typical for accreting X-ray pulsars. Based on the extended data set obtained with INTEGRAL and using the current ephemerides for LMC X-4 (Molkov et al 2015), we have repeated such an analysis and verified the result of Grebenev et al (2013).…”
Section: Sensitivity and Source Detectionmentioning
confidence: 99%
“…Nevertheless, taking into account a peculiar property of LMC X-4 (the source periodically goes to the "off"-state) and using the corresponding subset of revolutions, Grebenev et al (2013) showed that the persistent hard X-ray emission actually originates from the sky region coinciding with the position of another X-ray pulsar, EXO 053109-6609.2. This conclusion was supported by an independent detection of this source in the standard X-ray energy band by the INTEGRAL/JEM-X telescope, which allowed Grebenev et al (2013) to reconstruct the source spectrum in a broad energy band and demonstrate that it is typical for accreting X-ray pulsars. Based on the extended data set obtained with INTEGRAL and using the current ephemerides for LMC X-4 (Molkov et al 2015), we have repeated such an analysis and verified the result of Grebenev et al (2013).…”
Section: Sensitivity and Source Detectionmentioning
confidence: 99%
“…Using the same approach as in our previous Papers I-IX, we considered the IBIS surveys of , Krivonos et al (2010Krivonos et al ( , 2012, Coe et al (2010), Grebenev et al (2013), and the Swift/INTEGRAL ("SIX") joint catalogue of Bottacini et al (2012). Among them, we selected unidentified or unclassified hard X-ray sources containing a single bright soft X-ray object within the IBIS 90% confidence level error box.…”
Section: Sample Selectionmentioning
confidence: 99%
“…For the source naming in Table 1, we directly adopted the names as they appear in the relevant works Bottacini et al 2012;Ricci et al 2012;Coe et al 2010;Grebenev et al 2013;Krivonos et al 2010Krivonos et al , 2012, and the IGR alias when available. However, we remark that we chose not to use the ROSAT name as reported in the fourth IBIS Survey ) for one of the selected objects (1RXS J090320.0+533022), because the soft X-ray emission detected with Swift/XRT within the corresponding 90% IBIS error circle is not positionally consistent with the one reported in the ROSAT Faint Catalogue (actually, no detectable emission appears to be associated with this ROSAT object from Table 1).…”
Section: Sample Selectionmentioning
confidence: 99%
See 2 more Smart Citations